Tantangan Perlindungan Anak dalam Konflik Bersenjata: Analisis Kegagalan Struktural dalam Program UNICEF di Republik Afrika Tengah (International Forum of Researchers and Lecturers, 2025)
This research explores the key challenges in child protection efforts carried out by UNICEF in armed conflict areas, focusing on the case of the Central African Republic (CAR). It adopts a qualitative approach with a descriptive-analytical design, drawing on a literature review of UNICEF reports, UN documents, academic publications, and other credible sources. The analysis reveals that child protection failures stem not only from technical obstacles in the field but also from deeper structural problems, including the state’s weak presence, political compromises with armed groups, and limited institutional capacity. Three major categories of barriers are identified: structural and access-related obstacles, socio-cultural and political constraints, and institutional and operational limitations. UNICEF faces significant challenges in reaching high-risk areas, gaining community trust, and ensuring program sustainability amid high dependence on external funding. Using the human security framework, this research highlights the need to understand child protection in conflict zones as a multidimensional issue requiring a long-term, contextualized approach that strengthens state structures and empowers local communities.